Evaluation of M1 and M2 macrophages in ovarian endometriomas from women affected by endometriosis at different stages of the disease. (3rd May 2020) - Laganà, Antonio Simone; Salmeri, Francesca Maria; Ban Frangež, Helena; Ghezzi, Fabio; Vrtačnik-Bokal, Eda; Granese, Roberta
Abstract: Endometriosis is an estrogen-dependent disease defined by the presence and growth of functional endometrial-like tissue, glands and stroma, outside the uterine cavity. Macrophages are broadly classified into pro-inflammatory M1 macrophages, and M2 macrophages, which have selective anti-inflammatory and pro-fibrotic activities and are able to induce immunotolerance and angiogenesis. Based on these elements, the aim of our study was to evaluate CD14 + CD68 + CD197 + CD80 + M1 and CD14 + CD68 + CD163 + CD206 + M2 macrophages in tissue samples from ovarian endometriomas of women affected by endometriosis at different stages of the disease. For each patient, we collected a biological sample of the cyst (ovarian endometriomas for cases and ovarian functional cyst for controls) during laparoscopy. We found that the number of both M1 and M2 macrophages was significantly higher in endometriosis group than controls, regardless of stage ( p < .0001 for each stage versus controls). Moreover, our data analysis shows a trend in progressive decrease of M1 macrophages from stage I to stage IV; on the contrary, M2 macrophages show a specular trend compared to M1 macrophages, with a progressive increase from stage I to stage IV. This may contribute to the pro-inflammatory microenvironment in the early stages of the disease, and to the pro-fibrotic activity of the advanced stages.